2013
DOI: 10.1097/dbp.0b013e31829cafa6
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Sleep Interventions in the First Six Months of Life Do not Improve Outcomes for Mothers or Infants

Abstract: The belief that behavioral intervention for sleep in the first 6 months of life improves outcomes for mothers and babies is historically constructed, overlooks feeding problems, and biases interpretation of data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
101
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 107 publications
(130 reference statements)
2
101
0
2
Order By: Relevance
“…The predominant view is that formula feeding promotes infant sleep while breastfed infants are too demanding, feed too frequently, and do not allow their mothers sufficient sleep through the night (Ball, Hooker, & Kelly, 1999;Brown & Harries, 2015). In both the UK and the US, many parents give night-waking as the reason they switched to formula (Douglas & Hill, 2013) and the idea that feeding the infant formula before bed will help the whole family to sleep better is widely accepted (Rosen, 2008). Mothers are advised by peers and family to introduce formula or solid foods to the infant diet in order to promote longer periods of nocturnal sleep (Clayton, Li, Perrine, & Scanlon, 2013;Crocetti, Dudas, & Krugman, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The predominant view is that formula feeding promotes infant sleep while breastfed infants are too demanding, feed too frequently, and do not allow their mothers sufficient sleep through the night (Ball, Hooker, & Kelly, 1999;Brown & Harries, 2015). In both the UK and the US, many parents give night-waking as the reason they switched to formula (Douglas & Hill, 2013) and the idea that feeding the infant formula before bed will help the whole family to sleep better is widely accepted (Rosen, 2008). Mothers are advised by peers and family to introduce formula or solid foods to the infant diet in order to promote longer periods of nocturnal sleep (Clayton, Li, Perrine, & Scanlon, 2013;Crocetti, Dudas, & Krugman, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that breastfed babies sleep less, wake more or wake for longer than formula fed infants (Quillin & Glenn, 2004). In the last decade, an increasing number of studies have found that breastfeeding mothers and infants experience as much or more sleep than formula-feeding pairs, that breastfeeding mothers return to sleep more rapidly after overnight awakenings, and that hormonal mechanisms associated with breastfeeding may result in higher quality sleep (Doan, Gardiner, Gay, & Lee, 2007;Douglas & Hill, 2013;Montgomery-Downs, Clawges, & Santy, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ignoring the cue of sleepiness at the end of feeds and implementing feed-play-sleep cycles). 2,[4][5][6] In summary, Kempler et al's study confirms that high level evidence does not support the application of FWB approaches to parent-infant sleep, particularly in the first six months of life. Douglas and Hill's findings suggest that FWB approaches may even be detrimental to some families.…”
Section: High Level Evidence Does Not Support First Wave Behavioural mentioning
confidence: 93%
“…Our metanarrative review also concludes (p499): 'Application of behavioural methods from the first weeks of life increases self-regulated sleep periods and increases total 24-hour duration of time spent in the cot without signalling by 29 minutes.' 2 We then go on to argue that 'decreased episodes of night-waking or longer infant sleep durations do not inevitably improve outcomes for mothers and their infants, as is often assumed. '…”
Section: High Level Evidence Does Not Support First Wave Behavioural mentioning
confidence: 99%